Features of the initial stage of digitalization of the executive authority of Ukraine: historical and legal overview - E. Najafli (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the historical and legal analysis of the specifics of the process of primary digitization of the executive power in modernization in modern Ukraine (1993–2003), highlighting the main legal patterns of such a process. It is shown that the digitalization of the executive power has become a component of the only, in fact, process of digitalization of the public administration system in Ukraine, which covered all spheres, levels and segments of the functioning of state authorities and their interaction with citizens and society as a whole. Being a legal process, such digitization naturally required proper legal regulation both at the stage of introducing innovations regarding the use of ICT in the field of organization and activities of the executive power, and at the stage of implementing these innovations. The early stage of digitalization became the stage of informatization of the executive power in the context of the constitutional and legislative institutionalization of the executive power, when only the first legal steps regarding the initial digitalization in the context of the informatization of public administration were outlined. It is highlighted that this process continued within the stage of primary digitalization (1993–2003) without a clear conceptual vision of its political and legal essence, specificity and purpose of digitalization of the executive power, and its deployment in these conditions coincided in time with the unfinished institutionalization of the system of executive power bodies in Ukraine, which was determined first by the incompleteness of the constitutional process and the conceptual ambiguity of the constitutional model of the executive power system institutionalized in Ukraine (until 1996), and later by attempts to combine the digitalization of the executive power with attempts to reform it within the framework of the administrative reform paradigm (since 1998). It has been found that the key directions of digitalization of the executive power within this stage were the following: creation of the primary legal basis of digitalization; legitimization of informatization of state administration as one of the key functions of executive authorities; creation of the National Agency for Informatization under the President of Ukraine as an institutional center for the primary digitization of the executive power; legitimization of mandatory publication on the Internet of information about the activities of executive authorities; ensuring the functioning of websites of executive authorities of all levels on the basis of uniform standards, their unification and standardization; introduction of the Unified web portal of the Cabinet of Ministers of Ukraine, intended for the integration of official websites of executive authorities and placement of information resources in accordance with the needs of citizens; ensuring the coordination of work to ensure the functioning of the Unified web portal, its information content, technical support, support and establishment of regulations and standards for information exchange between its constituent parts; monitoring compliance with information protection requirements in information and telecommunication systems that ensure the content and functioning of official websites (web portals) of executive authorities and the Unified web portal; outline as a prospective task of the transition to a paperless (electronic) form of document circulation in the bodies of executive power.